Insights from interlanguage as revealed in writing: toward the development of metalinguistic competences for portuguese adult learners of English - Ribeiro, María del Carmen Arau (2015)
Based on a written corpus by 69 Portuguese learners of English, this study was designed to discover insights into the metalinguistic competences of young adult L2 users over three different sessions of a 30-hour a Technical English for Pharmacists at the School of Health of the Guarda Polytechnic Institute in Portugal. The longitudinal study effectively covered a total of 138 texts submitted as an initial and final report by each learner, written in conditions similar to those of the International Corpus of Learner English (ICLE). For the initial report, a portrait emerges of the written interlanguage of Portuguese science students after their K-12 course of study, with errors distributed among syntactic (43%), lexical (36%), and style and spelling (21%) sources. The written interlanguage analyzed consisted of 28,069 words, constituting 1,311 T-units, which revealed a total of 4,143 errors. The difference from the initial to the final report revealed an overall improvement of 6% less errors, from the pattern of 43-36-21% pattern for syntactic-lexical-style & spelling errors to 47-37-16%, after the 30-hour course. This was accompanied by a 42% growth in the number of words produced, and a corresponding increase of 17% in the number of T-units as well as a 23% rise in their mean length (MLT-U). These changes were further explored to determine that, of the three groups studied, one first and two second year groups, with average ages of 19 and 20.13 respectively, reveal age to be a significant factor for improvements, particularly in both the number of words and T-units. Error analysis determined an overall error recurrence of 45% syntactic, 37% lexical, and 18% due to style and spelling; further analysis found that, in six of the ten subclassifications, representing 57% of the written corpus, errors due to collocation, pronouns, Portuguese-influenced lexical choices, style, such as repetition and punctuation, and spelling showed patent improvement over the 30-hour course. The remaining 43%, distributed among four lexical and syntactic subclassifications in which more errors were revealed in the final reports at the end of the 30-hour course, lexical morphology and lexical choice as well as errors of distribution and production of verbal groups, were closely examined for insights into the metalinguistic competences of these subjects. Due to its exploratory nature, this study forged beyond L1 influence on errors, established at a total of 39% of the syntactical and lexical areas analyzed, to reveal a myriad of highly dynamic metalinguistic approaches to word formation and syntactic creation, the awareness of which can be productive for both learners and teachers. As such, the thesis concludes with a number of suggestions for best practice in the classroom based on the insights from interlanguage as revealed in writing.